2021
DOI: 10.47611/jsrhs.v10i2.1697
|View full text |Cite
|
Sign up to set email alerts
|

Minecraft Education Edition’s Ability to Create an Effective and Engaging Learning Experience

Abstract: Effective game-based learning is possible and incredibly important, as it provides effective, engaging, student-centered learning. While it has been successful for history learning,  effective game-based learning for STEM subjects is scarce. This study explored Minecraft Education Edition's chemistry features and their ability to create an effective and engaging learning experience, as Minecraft's game mechanics along with Education Edition's chemistry features may provide a solution to the lack of effective g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In this context, our proposal will provide tools to easily create virtual scenarios to connect students to STEM learning and also increase their interest and motivation [62]. Virtual scenarios will be presented in the context of a game, and gamification will be used to exploit their benefits [63,64].…”
Section: Related Workmentioning
confidence: 99%
“…In this context, our proposal will provide tools to easily create virtual scenarios to connect students to STEM learning and also increase their interest and motivation [62]. Virtual scenarios will be presented in the context of a game, and gamification will be used to exploit their benefits [63,64].…”
Section: Related Workmentioning
confidence: 99%
“…In the recent work (Panja and Berge, 2021) factors that should be considered when creating a game-based educational model are discussed. It has been indicated that not all students/players engage with Minecraft in the same way, and that prior game experience influences how the student learns (acquires knowledge), which affects the results.…”
Section: Game-based Learningmentioning
confidence: 99%
“…The game is used, among others, to learn science and technology. Initial research into the suitability of Minecraft for learning chemistry is described in (Panja and Berge, 2021). The factors that should be considered when building a Minecraft-based learning model are discussed.…”
Section: Recent Approaches Of Minecraft In Educationmentioning
confidence: 99%